Lightweight high-temperature titanium-based high-entropy alloy and preparation method thereof

By designing the TiAlCrNbVSi lightweight high-temperature titanium-based high-entropy alloy, the problems of insufficient strength, excessive density and poor room temperature processing performance at 600-700℃ are solved, and high strength, low density and good processing are achieved. Combination of performance, suitable for high-temperature structural parts.

CN119433288APending Publication Date: 2025-02-14BEIJING INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411631064.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The strength of high-temperature titanium-based alloys is not high enough at the operating temperature of 600-700℃, the density of some titanium-based high-temperature alloys is too large, and the processing performance of some titanium-based alloys is poor at room temperature.

Method used

A TiAlCrNbVSi-based lightweight high-temperature titanium-based high-entropy alloy was designed. By high entropy of the titanium-based high-temperature alloy, the alloy density was between 4.5g/cm3-4.9g/cm3, and it had BCC matrix phase + Ti3Al + Ti5Si3 precipitation phase. organizational structure.

Benefits of technology

At 600-700℃, the tensile strength of the alloy is significantly improved, the density is reduced, and the room temperature fracture strain is also improved. The material maintains high strength and plasticity at high temperatures, and is suitable for aircraft engine blades and spacecraft high-temperature structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433288A_ABST
    Figure CN119433288A_ABST
Patent Text Reader

Abstract

The invention discloses a light high-temperature titanium-based high-entropy alloy and a preparation method thereof, and particularly relates to a TiAlCrNbVSi light high-temperature titanium-based high-entropy alloy material and a preparation method thereof. The invention designs a lightweight high-temperature titanium-based high-entropy alloy with high strength at 600-700 DEG C. The lightweight high-temperature titanium-based high-entropy alloy is composed of TiaAlbCrcNbdVeSif, the atomic percent of a is 44-80%, the atomic percent of b is 10-20%, the atomic percent of c is 5-15%, the atomic percent of d is 0-12%, the atomic percent of e is 0-8%, and the atomic percent of f is 0-1%. Wherein b > c > = d > e, and a + b + c + d + e + f = 100%. The density of the alloy is 4.5-4.9 g / cm < 3 >. The tensile strength at room temperature is about 1.28 GPa, and the fracture strain is 3.5%. The tensile strength at 600 DEG C is 920 MPa, and the fracture strain is 6.7%; at the temperature of 650 DEG C, the tensile strength is 750 MPa, and the fracture strain is 16.3%; the tensile strength at 700 DEG C is 570 MPa, and the fracture strain is 45%. The obtained light high-temperature titanium-based high-entropy alloy has ultrahigh strength and certain plasticity, and the density is lower than 5 g / cm < 3 >; and meanwhile, the high-temperature alloy still has ultrahigh strength at 600-700 DEG C, and the strength of the high-temperature alloy is higher than that of a common titanium-based high-temperature alloy at 600-700 DEG C, so that the high-temperature alloy has great application potential in aero-engines and aerospace high-temperature structural parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high entropy alloys, and relates to a lightweight high-temperature titanium-based high-entropy alloy and a preparation method thereof, and in particular to a TiAlCrNbVSi series lightweight high-temperature titanium-based high-entropy alloy material and a preparation method thereof. Background Art

[0002] High-temperature titanium-based alloys refer to a type of titanium-based alloy that can be used for a long time at temperatures above 300°C. Initially, they were mainly near-α titanium alloys, and their use temperatures were mainly between 300-500°C. With the increase in the use temperature of high-temperature materials such as aircraft engine blades, two high-temperature titanium-based alloys, γ-TiAl alloy and Ti2AlNb, have been gradually developed. The use temperature of both alloys can reach 700°C, and they can still maintain a strength of about 400-700MPa at high temperatures of 600-700°C.

[0003] High entropy alloy refers to a type of alloy with four or more metal elements as the main elements (atomic molar ratio>5). Compared with traditional alloys, it has high entropy effect, lattice distortion effect, hysteresis diffusion effect and cocktail effect. Lightweight high entropy alloy refers to a material with a density of less than 5g / cm 3 High entropy alloys generally have the advantages of high strength, low density and high specific strength.

[0004] Among the current high-temperature titanium-based alloys, the use temperature of near-α titanium alloys such as Ti60 and TC11 alloys cannot exceed 600℃, and the strength of the alloy will be greatly reduced above this temperature. However, the tensile fracture strain of γ-TiAl alloys such as Ti-45Al2Cr2Nb1Mo at room temperature is less than 2%, and there is a problem of very poor machinability at room temperature. At the same time, its use strength at 600-650-700℃ is about 650-580-450MPa, and the use strength in this temperature range is not high enough. The density of Ti2AlNb alloy is about 5.2-5.5g / cm3, which has a problem of higher density than general titanium-based alloys. At the same time, its use strength at 600-650-700℃ is about 750-650-500MPa, and there is also a problem of insufficient use strength.

[0005] In order to solve the problems currently encountered by titanium-based high-temperature alloys, the present invention combines the design concepts of titanium-based high-temperature alloys and lightweight high-entropy alloys, and obtains a TiAlCrNbVSi series lightweight high-temperature titanium-based high-entropy alloy by high-entropy treatment of titanium-based high-temperature alloys, thereby obtaining a new alloy with better high-temperature performance while maintaining the basic advantages of titanium-based high-temperature alloys. Summary of the invention

[0006] The main purpose of the present invention is to solve the problem that the strength of high-temperature titanium-based alloys is not high enough at the use temperature of 600-700℃, the density of some titanium-based high-temperature alloys is too large, and the room temperature processing performance of some titanium-based alloys is poor. First, for titanium-based high-temperature alloys, the use strength at 600-700℃ is the most important mechanical performance index. The higher the strength, the stronger the reliability as a high-temperature structural part. At present, the use strength of titanium-based high-temperature alloys at 600℃ is about 600-750MPa, and the use strength at 700℃ is about 400-500MPa. Second, such as Ti2AlNb titanium-based high-temperature alloy, its density is about 5.4g / cm3, which is higher than general light alloys (<5g / cm3). The increase in density will increase the overall mass of the structural parts. Third, such as γ-TiAl alloy, the tensile fracture strain at room temperature is less than 2%, and most γ-TiAl cannot even be subjected to tensile tests, resulting in its inability to be accurately machined.

[0007] Therefore, the present invention combines the design concepts of titanium-based high-temperature alloys and high-entropy alloys to design a TiAlCrNbVSi series lightweight high-temperature titanium-based high-entropy alloy, with the aim of solving the problem of insufficient strength of titanium-based high-temperature alloys at 600-700°C, while ensuring that the alloy has certain machinability at room temperature and that the alloy density is not higher than 5g / cm3.

[0008] The present invention discloses a lightweight, high-temperature titanium-based high-entropy alloy, which is composed of TiaAlbCrcNbdVeSif, wherein:

[0009] The atomic percentage of a is 44-80%;

[0010] The atomic percentage of b is 10-20%;

[0011] The atomic percentage of c is 5-15%;

[0012] The atomic percentage of d is 0-12%;

[0013] The atomic percentage of e is 0-8%

[0014] The atomic percentage of f is 0-1%

[0015] And b>c≥d>e, a+b+c+d+e+f=100%.

[0016] Furthermore, the lightweight high-temperature titanium-based high-entropy alloy is Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 .

[0017] The present invention also discloses a method for preparing a TiaAlbCrcNbdVeSif lightweight high entropy alloy material, comprising the following steps:

[0018] (1) Weigh the single-element Ti, Al, Cr, Nb, V and Si particles according to atomic percentage;

[0019] (2) The weighed materials are placed in a non-consumable vacuum induction melting furnace for melting, and Al, Si, Ti, V, Cr and Nb are placed in order from low to high melting points. After they are completely melted, they are cooled by heat preservation.

[0020] (3) Turn the ingot over and melt it repeatedly for several times, then keep it warm and cool.

[0021] (4) The ingot is cast into a water-cooled copper crucible and cooled by water to obtain an ingot.

[0022] Furthermore, the single substance in step (1) is also ultrasonically rinsed with anhydrous ethanol before weighing.

[0023] Furthermore, the vacuum melting furnace in step (2) is equipped with a 20°C cooling device, which is water-cooled.

[0024] Furthermore, before smelting in step (2), the vacuum smelting furnace body is first subjected to a gas washing operation: the furnace is first evacuated to a vacuum until the vacuum degree is less than 9.9*10 -4 Pa, argon with a purity of 99.9% is injected, and the inflation is stopped when the pressure in the furnace reaches -0.5MPa; after standing for 10-20 minutes, the second vacuum washing operation is carried out.

[0025] Furthermore, the voltage of the vacuum melting in step (2) is set to 300V and the current is set to 25A.

[0026] Furthermore, the insulation time in step (2) is 15 seconds.

[0027] Furthermore, the smelting times in step (3) is 5 times.

[0028] Furthermore, during the third and fourth smelting, magnetic stirring is turned on to make the high entropy alloy master alloy ingot more uniform.

[0029] Furthermore, the present invention can also adjust the strength and hardness of the alloy by adjusting the Al content; adjust the strength of the alloy by adjusting the Cr content; adjust the plasticity of the alloy by adjusting the Nb content; adjust the toughness of the alloy by adjusting the V content; or adjust the high temperature strength of the alloy by adjusting the Si content.

[0030] The present invention also discloses a TiaAlbCrcNbdVeSif lightweight high entropy alloy material prepared by any of the above preparation methods.

[0031] The beneficial effects of the present invention are:

[0032] Compared with the existing technology, the present invention is based on Ti, and Al, Cr, Nb, V and Si are added as main elements to form a lightweight high entropy alloy with a density of 4.5g / cm 3 -4.9g / cm 3 Through the observation of the organization and the test of mechanical properties, its organization is BCC matrix phase + Ti3Al precipitation phase + Ti5Si3 precipitation phase, and its tensile strength at room temperature is 1280MPa, and the fracture strain is 3.5%; the tensile strength at 600℃ is 920MPa, and the fracture strain is 6.7%; the tensile strength at 650℃ is 750MPa, and the fracture strain is 16.3%; the tensile yield strength at 700℃ is 570MPa, and the fracture strain is 45%. Compared with the γ-TiAl alloy, the TiaAlbCrcNbdVeSif lightweight high-temperature titanium-based high-entropy alloy of the present invention has an increase of about 43% in tensile strength at 600℃; 35% in tensile strength at 650℃; and about 20% in tensile strength at 700℃; and the fracture strain at room temperature is increased by about 50%. Compared with Ti2AlNb, its tensile strength at 600°C is increased by about 28%; at 650°C, the tensile strength is increased by about 22%; at 700°C, the tensile strength is increased by about 17%, and the density of the alloy is reduced by about 10%. The use temperature is significantly improved compared with near-α titanium alloys. The TiaAlbCrcNbdVeSif lightweight high-temperature titanium-based high-entropy alloy of the present invention has a tensile strength far exceeding that of general titanium-based high-entropy alloys at 600-700°C, and a density of less than 5g / cm3, and a fracture strain of 3.5% at room temperature. At the same time, the material design method is simple, the preparation process is economical and efficient, and the casting process has high molding efficiency. It has a strong prospect for use in the field of aircraft engine blades and high-temperature structural parts of spacecraft. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 SEM microstructure of the alloy;

[0034] Figure 2 It is Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 X-ray diffraction pattern of the alloy;

[0035] Figure 3 It is Ti 60.6 Al 16 Cr10 Nb8V5Si 0.4 Room temperature quasi-static tensile stress-strain curves of the alloy;

[0036] Figure 4 It is Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 High temperature quasi-static compressive stress-strain curves of the alloy. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0038] Example 1

[0039] A lightweight high-temperature titanium-based high-entropy alloy, comprising Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 Alloy, the alloy is BCC+Ti3Al+Ti5Si3 structure, such as Figure 2 shown.

[0040] A lightweight high-temperature titanium-based high-entropy alloy Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 The specific steps of the preparation method are as follows:

[0041] (1) Select six elements, Ti, Al, Cr, Nb, V and Si, and weigh the corresponding mass of Ti, Al, Cr, Nb, V and Si according to the atomic molar ratio. Put the elements into the copper crucible of the non-consumable vacuum induction melting furnace in the order of the melting points of the raw materials from high to low, i.e. Al, Si, Ti, V, Cr and Nb.

[0042] (2) The furnace door is closed, and the non-consumable vacuum induction melting furnace is evacuated to a vacuum state, and then high-purity argon gas with a purity of 99.99% is introduced as a protective gas.

[0043] (3) Repeated smelting of Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 The alloy was smelted 5 times, with a smelting current of 25A, a smelting voltage of 300V, and each smelting time of 3min. After the smelting was completed, the alloy was cooled and the ingot was taken out.

[0044] (4) The ingot was cut and sampled. The density of the alloy was measured by the Archimedes drainage method and was 4.82 g / cm 3Then XRD and SEM tests were performed, and the results were as follows: Figure 1 and 2 As shown; room temperature quasi-static stretching and high temperature quasi-static stretching tests were performed simultaneously, and the results were as follows Figure 3 and 4 As shown. XRD test results show that Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 The lightweight high-temperature titanium-based high-entropy alloy is composed of BCC matrix + Ti3Al and Ti5Si3 precipitation phases; equiaxed BCC phases can be observed in SEM images. Mechanical properties test results show that Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 The lightweight, high-temperature titanium-based high-entropy alloy has a room temperature tensile strength of 1280MPa and a fracture strain of 3.5%; the tensile strength at 600°C is 920MPa and the fracture strain is 6.5%; the tensile strength at 650°C is 750MPa and the fracture strain is 16.3%; the tensile strength at 700°C is 570MPa and the fracture strain is 45%.

[0045] Example 2

[0046] A lightweight high-temperature titanium-based high-entropy alloy, comprising Ti 60.2 Al 16 Cr 10 Nb8V5Si 0.8 Alloy, the alloy has a BCC+Ti3Al+Ti5Si3 structure.

[0047] A lightweight high-temperature titanium-based high-entropy alloy Ti 60.2 Al 16 Cr 10 Nb8V5Si 0.8 The preparation method comprises the following specific steps:

[0048] (1) Select six elements, Ti, Al, Cr, Nb, V and Si, and weigh the corresponding mass of Ti, Al, Cr, Nb, V and Si according to the atomic molar ratio. Put the elements into the copper crucible of the non-consumable vacuum induction melting furnace in the order of the melting points of the raw materials from high to low, i.e. Al, Si, Ti, V, Cr and Nb.

[0049] (2) The furnace door is closed, and the consumable vacuum arc melting furnace is evacuated to a vacuum state, and then high-purity argon gas with a purity of 99.99% is introduced as a protective gas.

[0050] (3) Repeated smelting of Ti 60.2 Al 16 Cr10 Nb8V5Si 0.8 The alloy was smelted 5 times, with a smelting current of 25A, a smelting voltage of 300V, and each smelting time of 3min. After the smelting was completed, the alloy was cooled and the ingot was taken out.

[0051] Archimedes drainage method was used to 60.2 Al 16 Cr 10 Nb8V5Si 0.8 The density of the lightweight high entropy alloy was tested and found to be 4.81 g / cm 3 , room temperature quasi-static tensile tests and high temperature quasi-static tensile tests were carried out at the same time. The mechanical properties test results showed that Ti 60.2 Al 16 Cr 10 Nb8V5Si 0.8 The lightweight, high-temperature titanium-based high-entropy alloy has a room temperature tensile strength of 1390 MPa and a fracture strain of 1.3%; the tensile strength at 600°C is 1030 MPa and the fracture strain is 2.5%; the tensile strength at 650°C is 860 MPa and the fracture strain is 6.3%; the tensile strength at 700°C is 710 MPa and the fracture strain is 21%.

[0052] Example 3

[0053] A lightweight high-temperature titanium-based high-entropy alloy, comprising Ti 49.6 Al 20 Cr 15 Nb 10 V5Si 0.4 Alloy, the alloy has a BCC+Ti3Al+Ti5Si3 structure.

[0054] A lightweight high-temperature titanium-based high-entropy alloy Ti 49.6 Al 20 Cr 15 Nb 10 V5Si 0.4 The preparation method comprises the following specific steps:

[0055] (1) Select six elements, Ti, Al, Cr, Nb, V and Si, and weigh the corresponding mass of Ti, Al, Cr, Nb, V and Si according to the atomic molar ratio. Put the elements into the copper crucible of the non-consumable vacuum induction melting furnace in the order of the melting points of the raw materials from high to low, i.e. Al, Si, Ti, V, Cr and Nb.

[0056] (2) The furnace door is closed, and the consumable vacuum arc melting furnace is evacuated to a vacuum state, and then high-purity argon gas with a purity of 99.99% is introduced as a protective gas.

[0057] (3) Repeated smelting of Ti49.6 Al 20 Cr 15 Nb 10 V5Si 0.4 The alloy was smelted 5 times, with a smelting current of 25A, a smelting voltage of 300V, and each smelting time of 3min. After the smelting was completed, the alloy was cooled and the ingot was taken out.

[0058] Archimedes drainage method was used to 49.6 Al 20 Cr 15 Nb 10 V5Si 0.4 The density of the high entropy alloy was tested and the density was found to be 4.88 g / cm 3 , and high temperature quasi-static tensile tests were carried out at the same time. The test results showed that Ti 60.2 Al 16 Cr 10 Nb8V5Si 0.8 The lightweight high-temperature titanium-based high-entropy alloy has a tensile strength of 970 MPa and a fracture strain of 3.3% at 650°C; the tensile strength is 790 MPa and the fracture strain is 9% at 700°C.

[0059] Example 4

[0060] A lightweight high-temperature titanium-based high-entropy alloy, comprising Ti 74.6 Al 10 Cr8Nb5V2Si 0.4 Alloy, the alloy has a BCC+Ti3Al+Ti5Si3 structure.

[0061] A lightweight high-temperature titanium-based high-entropy alloy Ti 74.6 Al 10 Cr8Nb5V2Si 0.4 The preparation method comprises the following specific steps:

[0062] (1) Select six elements, Ti, Al, Cr, Nb, V and Si, and weigh the corresponding mass of Ti, Al, Cr, Nb, V and Si according to the atomic molar ratio. Put the elements into the copper crucible of the non-consumable vacuum induction melting furnace in the order of the melting points of the raw materials from high to low, i.e. Al, Si, Ti, V, Cr and Nb.

[0063] (2) The furnace door is closed, and the consumable vacuum arc melting furnace is evacuated to a vacuum state, and then high-purity argon gas with a purity of 99.99% is introduced as a protective gas.

[0064] (3) Repeated smelting of Ti 74.6 Al 10 Cr8Nb5V2Si 0.4The alloy was smelted 5 times, with a smelting current of 25A, a smelting voltage of 300V, and each smelting time of 3min. After the smelting was completed, the alloy was cooled and the ingot was taken out.

[0065] Archimedes drainage method was used to 74.6 Al 10 Cr8Nb5V2Si 0.4 The density of the lightweight high entropy alloy was tested and found to be 4.63 g / cm 3 , and high temperature quasi-static tensile tests were carried out at the same time. The test results showed that Ti 60.2 Al 16 Cr 10 Nb8V5Si 0.8 The lightweight high-temperature titanium-based high-entropy alloy has a tensile strength of 760MPa and a fracture strain of 15.2% at 600°C; a tensile strength of 620MPa and a fracture strain of 26.3% at 650°C; and a tensile strength of 450MPa and a fracture strain of >50% at 700°C.

[0066] The above is a description of the preferred embodiments of the present invention. It should be noted that the present invention is not limited to the above embodiments, and any modification, equivalent replacement or improvement of the present invention, etc., which meets the scope requirements of the claims, the content of the invention and the drawings, shall be included in the protection scope of the present invention.

Claims

1. A lightweight, high-temperature titanium-based high-entropy alloy, the chemical composition of which is: TiaAlbCrcNbdVeSif; wherein: The atomic percentage of a is 44-80%; The atomic percentage of b is 10-20%; The atomic percentage of c is 5-15%; The atomic percentage of d is 0-12%; The atomic percentage of e is 0-8% The atomic percentage of f is 0-1% And b>c≥d>e, a+b+c+d+e+f=100%.

2. The lightweight, high-temperature titanium-based high-entropy alloy according to claim 1, wherein: The TiaAlbCrcNbdVeSif is Ti 60.6 Al 16 Cr 10 Nb8V5Si 0.4 .

3. A method for preparing a lightweight, high-temperature titanium-based high-entropy alloy as claimed in claim 1 or 2, comprising: (1) Weigh each element: weigh the single elements Ti, Al, Cr, Nb, V and Si according to atomic percentage; (2) Melting to prepare high entropy alloy: The weighed raw materials are placed in a non-consumable vacuum induction melting furnace, the vacuum degree is adjusted, argon protective gas is filled in for washing, the melting is repeated for a preset number of times, and the temperature is kept and cooled to obtain a lightweight, high-temperature titanium-based high entropy alloy.

4. The preparation method according to claim 3, wherein: The purity of the argon gas in step (2) is 99.99wt%.

5. The preparation method according to claim 3, wherein: When the vacuum degree in step (2) is less than 9.9×10-4, argon gas is introduced, and the inflation is stopped when the vacuum degree reaches -0.5 MPa; After standing for 10-20 minutes, perform the second vacuum cleaning operation.

6. The preparation method according to claim 3, wherein: The preset number of smelting times in step (2) is 5 times.

7. The preparation method according to claim 6, wherein: When the smelting is performed for the third and fourth times, magnetic stirring is turned on.

8. The preparation method according to claim 3, wherein: The holding time in step (2) is 15 seconds.

9. The preparation method according to claim 3, wherein: The smelting voltage in step (2) is 300V and the current is 25A.

10. A lightweight, high-temperature titanium-based high-entropy alloy prepared according to any one of the preparation methods described in claims 3 to 9.